Towards an Understanding of Li2O2 Evolution in Li–O2 Batteries: An In Operando Synchrotron X‐ray Diffraction Study. Issue 7 (1st March 2017) - Liu, Chenjuan; Brant, William R.; Younesi, Reza; Dong, Yanyan; Edström, Kristina; Gustafsson, Torbjörn; Zhu, Jiefang
Abstract: One of the major challenges in developing high‐performance Li–O2 batteries is to understand the Li2 O2 formation and decomposition during battery cycling. In this study, this issue was investigated by synchrotron radiation powder X‐ray diffraction. The evolution of Li2 O2 morphology and structure was observed under actual electrochemical conditions of battery operation. By quantitatively tracking Li2 O2 during discharge and charge, a two‐step process was suggested for both growth and oxidation of Li2 O2 owing to different mechanisms during two stages of both oxygen reduction reaction and oxygen evolution reaction. From an observation of the anisotropic broadening of Li2 O2 in XRD patterns, it was inferred that disc‐like Li2 O2 grains are formed rapidly in the first step of discharge. These grains can stack together so that they facilitate the nucleation and growth of toroidal Li2 O2 particles with a LiO2 ‐like surface, which could cause parasitic reactions and hinder the formation of Li2 O2 . During the charge process, Li2 O2 is firstly oxidized from the surface, followed by a delithiation process with a faster oxidation of the bulk by stripping the interlayer Li atoms to form an off‐stoichiometric intermediate. This fundamental insight brings new information on the working mechanism of Li–O2 batteries. Abstract : A closer look at lithium batteries : The evolution of Li2 O2 is investigated by in operando synchrotron radiation powder X‐ray diffraction to establish the mechanisms in the oxygen reduction reaction and the oxygen evolution reaction during the first cycle by using a 1, 2‐dimethoxyethane electrolyte system. By quantitatively tracking Li2 O2 during cycling, a two‐step process is suggested for both growth and oxidation of Li2 O2 .